The Effect of Local Anaesthetics and Antiarrhythmic Agents on the Responses of Rabbit Platelets to ADP and Thrombin - Anderson, Esther R; Foulks, J G; Godin, D V (Thrombosis and Haemostasis, 1981)
Local anaesthetics and antiarrhythmic agents produced changes in responses of rabbit platelets to ADP and thrombin that varied with the agent and its concentration. In high concentrations all local anaesthetics decreased aggregation rates. At lower concentrations several local anaesthetics increased aggregation rates. Depending on the agonist and local anaesthetic, increases were produced at all or only at low or high agonist concentrations. Local anaesthetics failed to influence shape change except at concentrations much greater than those which inhibited aggregation. Inhibition of aggregation by procaine was potentiated by small organic anions suggesting effects at different sites on the platelet membrane. The inhibitory effect of local anaesthetics was decreased by increasing Ca. Kinetic analysis indicated different mechanisms for this Ca effect, i. e., predominantly competitive for procaine or lidocaine and predominantly non-competitive for tetracaine or ethyl lidocaine. Local anaesthetics may affect aggregation by modifying the participation of Ca in this process.
Keywords: Platelets; Aggregation; Local anaesthetics; Antiarrhythmic agents